THE BEHAVIOR OF FOOT CARE IN PATIENTS WITH TYPE 2 DIABETES MELLITUS: APPLYING THE THEORY OF PLANNED BEHAVIOUR - Narmawan, Narmawan; Syahrul, Syahrul; Erika, Kadek Ayu (Public Health of Indonesia, 2018)
Background: Diabetes mellitus (DM) is a chronic non-infectious disease with complications such as diabetic foot, which has the potential for amputation if left untreated. Theory of Planned Behavior (TPB) is a behavior-based theory that can be applied to DM patients including foot care to minimize risk. Some studies related to TPB particularly about physical activity and diet have been explored, however, studies on foot care are still lacking.Objective: This study aims to apply the Theory of Planned Behavior (Intentions, Attitudes, Subjective Norms and Behavioral Control) on the patient's foot care.Methods: This was a cross sectional descriptive study. There were 93 patients diagnosed with type 2 DM recruited at 9 public health centers (Puskesmas) using accidental sampling on April 2018. TPB-based foot care questionnaire from the IWGDF (International Working Group on Diabetic Foot) Diabetic Foot guidelines was used. Data were analyzed in the form of frequency distribution.Results: Of the total number of respondents, 25 males and 68 females with average age of 53.05 ± 8.04 years, approximately 87.1% of them have the intention to wear footwear according to size. The majority of patients think that washing feet every day is a form of good and positive practice. They also agreed that the family expects the patient to examine the presence of bone / joint protrusions independently and believes that monitoring the foot deformities performed by other DM patients is very important as well as having control that the patient can check for signs of boils in the legs and there is a high likelihood of blisters / sores if the socks used are not suitable.Conclusion: The majority of respondents have good intentions, positive attitudes, social support and behavioral controls for foot care.